Effect of Ground and foliar fertilization using Humzinc compound on some growth and yield characters of wheat (Triticum aestivum L.): Issa T. Khalaf* Bassima A. Assal** R. R. Araak** - طالب خلف, عيسى; عذار عسل, باسمة; ريس عراك, رنا (Journal of Kerbala for Agricultural Sciences, 2017)
An experiment was carried out to study the effect of ground and foliar application on some growth and yield characters of wheat. The compound Humzinc being used with the components 40% humic acid , 3.5% , 2.5% and 1.5% for pelleted Fe , Zn and Mn respectively , resulting from dissolving 10 gm in 10 liter of Water. The experiment included 9 treatments by increasing the weights above 10 gm (comparny recommendation) symmetrically up to 24 gm in 10 liter of water sprayed at two growth stages (after tillering and heading). 100 kgN / ha-1 + 100 kg P ha-1 was used as a ground fertilization. The results showed that ground application + 24 gm in 10 liter of water gave the best results in stem height (cm) and flag leaf area (cm2). The ground fertilization treatment had the lowest means. In general there were no significant differences between the fertilization treatments at high levels of spraying. Thus there was a decrease trend in leaf numbers. Spraying at heading gave the best results for the overall studied growth characters. With the interaction , the treatment ground application + 24 gm in 10 liter of water sprayed at heading had the highest means. That effect was persisted on yield components , yield and biological yields , whereas , the ground application + 24 gm in 10 liter of water gave the best results. But , there was no significant differences between the ground application treatment and other foliar spraying treatments. In general spraying the compound at high concentrations doubled the grain yield. The treatment ground fertilization + 24 gm in 10 liter of water gave 8.18 ton ha-1 compared with 4.81 ton ha-1 at basal application only. Key words : ground application , Foliar spraying , Mineral compound , soft wheat , Scientific nomination, variety produced in IPA agriculture centre , pelleted ferrous , Zinc and Manganese.